Peningkatan Kompetensi Guru PAUD Dalam Melaksanakan Pembelajaran Berbasis Konsep Merdeka Bermain Di Kecamatan Maro Sebo Ulu Kabupaten Batanghari - Herwina Dewi Librianty; Yennizar N; Novi Susanti; Hikmah.M (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Implementation the concept of ‘merdeka bermain’ in the realm of Early Childhood Education (PAUD) requires a change in the role of the teacher who was originally always the center of learning and places the play environment as the main medium for developing children's curiosity and involvement. The teacher's role is more directed at its function as a motivator and facilitator. Therefore, it is very important to socialize the concept of ‘merdeka bermain’ to improve teacher competence. This service aims to: 1)Improve teacher competence in understanding the concept of ‘merdeka bermain’; 2)Improving the competence of teachers in understanding and carrying out their roles as motivators and facilitators in learning; 3)Improving teacher competence in implementing independent play-based learning practices by utilizing local potential. The method of this service activity uses the following approaches: training, technical guidance and mentoring. Results: 1)Increased teacher understanding of the concept of merdeka bermain’; 2)Increasing the ability of teachers in their roles as motivators and facilitators; 3)Increased understanding of teachers in the practice of free play-based learning. The limitations in this assistance are due to the time and available funds. The hope in the future is further assistance for teachers so that they can carry out the indicators of independent play-based learning more comprehensively, especially in designing the variety of play; Optimizing the environment as a learning resource; as well as the sharpness and accuracy of the assessment targets